The tale of Timmy Tiptoes. - Potter, Beatrix, 1866-1943. (New York : F. Warne, 1939)
Timmy Tiptoes, a comfortable little grey squirrel, runs into trouble with his fellow squirrels over the hoarding of nuts for the winter.
Keywords: Squirrels -- Fiction